Vitamin D supplementation reduces the risk of preeclampsia in high-risk pregnant females - Safdar, Mehwish; Zafar, Humaira; Irfan, Shakeela; Naz, Mubashra; Fatima, Anees; Fatima, Umber; Yameen, Attiya (International Journal of Research in Medical Sciences, 2022)
Background: Maternal vitamin D insufficiency has been linked with increased risk of preeclampsia. Despite this, the evidence regarding the efficacy of vitamin D supplementation in preventing preeclampsia is controversial. The aim of study was to collate the incidence of preeclampsia in high-risk females with vitamin D supplementation versus placebo. Methods: The present study was a randomized controlled trial. The study was conducted in the department of obstetrics and gynecology, Madinah Teaching Hospital affiliated with University Medical and Dental College Faisalabad. The study was collected over one year from July 2019 to June 2020. Patients were randomly assigned to two groups. Patients in group-A were given vitamin D supplementation of 600 IU daily. The control group (group-B) was given placebo. If blood pressure (BP) ≥140/90 mmHg and proteinuria found positive in urine, then preeclampsia was labeled (as per operational definition). Both groups were compared for preeclampsia by using Chi–square test. P value <0.05 was taken as significant. Results: The incidence of preeclampsia was 4% (n=2/150) in group A and 8% (n=6/150) in group B developed preeclampsia. The difference was (p value=0.3) insignificant difference. Conclusions: Vitamin D addition in pregnancy did not demonstrate a statistically significant effect of vitamin D on the prevention of preeclampsia.